Million dollar consulting : the professional's guide to growing a practice - Weiss, Alan, 1946- (McGraw-Hill, 2016)
Build a thriving consultancy with the updated edition of this classic bestseller Having inspired generations of consultants and entrepreneurs around the world, the "Rock Star of Consulting" Alan Weiss returns with a revised and completely updated edition of his authoritative guide to consulting success. Weiss provides his time-tested model on creating a flourishing consulting business, while incorporating and focusing on the many dynamic changes in solo and boutique consulting, coaching, and entrepreneurship. In addition to guidance on raising capital, attracting clients, and creating a marketing plan, he also gives brand new step-by-step advice on: * Harnessing today's global opportunities * Developing brands across markets * Creating and licensing intellectual property * Avoiding the pitfalls of social media * Landing unsolicited referrals through counterintuitive methods * Managing and organizing your time wisely * Succeeding in the face of continuing turbulence Find out why this book has been the classic go-to for consultants for nearly twenty-five years, and learn how to grow your business into a $1 million-per-year firm today!. --Provided by publisher